On dihedral hypergroups. (February 2015) - Jafarpour, M.; Cristea, I.; Alizadeh, F.
Abstract: In this paper the notion of ψ -dihedral hypergroups is introduced as a generalization of dihedral groups. Basic properties of these algebraic structures are considered; we particularly insist on the regularity property of this kind of hypergroups.